The involvement of beta-1,4-galactosyltransferase and N-acetylglucosamine residues in fertilization has been lost in the horse - Magistrini Michèle (Reproductive Biology and Endocrinology, 2008)
Abstract Background In human and rodents, sperm-zona pellucida binding is mediated by a sperm surface Galactosyltransferase that recognizes N-Acetylglucosamine residues on a glycoprotein ZPC. In large domestic mammals, the role of these molecules remains unclear: in bovine, they are involved in sperm-zona pellucida binding, whereas in porcine, they are not necessary. Our aim was to clarify the role of Galactosyltransferase and N-Acetylglucosamine residues in sperm-zona pellucida binding in ungulates. For this purpose, we analyzed the mechanism of sperm-zona pellucida interaction in a third ungulate: the horse, since the Galactosyltransferase and N-Acetylglucosamine residues have been localized on equine gametes. Methods We masked the Galactosyltransferase and N-Acetylglucosamine residues before the co-incubation of gametes. Galactosyltransferase was masked either with an anti-Galactosyltransferase antibody or with the enzyme substrate, UDP Galactose. N-Acetylglucosamine residues were masked either with a purified Galactosyltransferase or with an anti-ZPC antibody. Results and discussion The number of spermatozoa bound to the zona pellucida did not decrease after the masking of Galactosyltransferase or N-Acetylglucosamine. So, these two molecules may not be necessary in the mechanism of in vitro sperm-zona pellucida interaction in the horse. Conclusion The involvement of Galactosyltransferase and N-Acetylglucosamine residues in sperm-zona pellucida binding may have been lost during evolution in some ungulates, such as porcine and equine species.